Evaluation of antimicrobial activity of some compounds for purulent wounds treatment - Mishyna, Marina M.; Burov, Andrey N.; Vekshyn, Vitaliy A.; Grabovetskaya, Evgeniya R. (Journal of Education, Health and Sport, 2021)
Results of in vitro studies of antimicrobial compounds effect on clinical strains Staphylococcus aureus and Pseudomonas aeruginosa, causing purulent inflammation of open wounds are considered in the article. Activity of the compounds was determined according to the inhibition of the microorganisms growth by means of agar well diffusion method. Nisin and silver nitrate are shown to exhibit antimicrobial properties, while such classical antiseptics as ectericide and colloidal silver were inactive.